2013
DOI: 10.1016/j.gaitpost.2012.07.027
|View full text |Cite
|
Sign up to set email alerts
|

The influence of wrist posture on the time and frequency EMG signal measures of forearm muscles

Abstract: This study investigates how altering wrist posture influences the relationship between the time and frequency measures of the electromyography (EMG) signal of extensor digitorum communis (EDC) and flexor carpi ulnaris (FCU). Thirteen participants exerted handgrip force related to maximum voluntary contraction (MVC) in four tests: 20%MVC and 50%MVC in neutral wrist posture and 20%MVC in full wrist flexion and extension. EMG measurements from EDC and FCU were used to calculate normalized values of amplitude (nRM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 26 publications
2
33
0
Order By: Relevance
“…Roman-Liu and Bartuzi [18] analyses chosen sections of the EMG signal and divided them into parts. Out of them, they chose 3-second sections with the most stable value of the amplitude.…”
Section: Data Processing and Difficulties In Interpreting The Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Roman-Liu and Bartuzi [18] analyses chosen sections of the EMG signal and divided them into parts. Out of them, they chose 3-second sections with the most stable value of the amplitude.…”
Section: Data Processing and Difficulties In Interpreting The Resultsmentioning
confidence: 99%
“…Before each measurement, the skin shall be properly prepared and its condition shall be checked so that between the electrode and the skin the resistance is not too large because it influences the result of the test. The skin is disinfected with an alcohol swab, shaved and disinfected one more time [18]. Another method of preparing the skin is wiping it with abrasive paper (in order to remove the outer layer of the epidermis) after prior shaving and then disinfecting it with alcohol [19].…”
Section: Techniques and Standards Of Performancementioning
confidence: 99%
See 1 more Smart Citation
“…However, others reported a decrease in muscle length resulting in a decrease in EMG amplitude [17]. Roman-Liu and Bartuzi [18] showed that a decrease in muscle length caused by altering the wrist posture influenced the relationship between the time and frequency measures in forearm muscles, whereas an increase in muscle length did not. Studies on BB [19,20] and TB [20] showed an increase in spectral parameters such as MF and MPF when the length of muscle decreased.…”
Section: Discussionmentioning
confidence: 98%
“…The MPF we observed was 130 ± 33 H z at 100% MVC. Roman‐Liu and Bartuzi observed an MPF of 121 ± 28 H z while participants performed isometric contractions of the wrist flexors at 50% MVC. The higher MPF we observed was most likely due to muscle fiber conduction velocity changes between 50% and 100% MVC .…”
Section: Discussionmentioning
confidence: 99%